PENGGUNAAN METODE DISCOVERY DENGAN MEDIA REALIA DALAM PENINGKATAN PEMBELAJARAN IPA DI KELAS IV SDN 1 KEDUNGWINANGUN TAHUN PELAJARAN 2014/ 2015 - kuswati, wiji (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Use of Discovery Method with Realia Media in Improvement of Science Learning At the Fourth Grade Student of SDN 1 Kedungwinangunin academic year of 2014/2015 . The purpose were describe the improvement of science learning by the use of discovery method with realia media at the fourth grade student of SDN 1 Kedungwinangun in academic year of 2014/2015. The results show that the use of discovery method with realia media can improve science learning at the fourth grade students. The completeness results of studying the pretest was 14,29% of all students, become 39,29% in cycle I, 66,07% in cycle II, and 87,50% in cycle III. Keywords: discovery method, realia media, sciences learning